Michael Pye, Translating Drunk: and Stark Naked Problems in Presenting Eighteenth Century Japanese Thought - Barrett, Timothy (Journal of the Irish Society for the Academic Study of Religions, 2016)
In 1990 Michael Pye published a full translation of the writings of the Japanese scholar Tominaga Nakamoto (1715-1746), to which I responded in a 1993 review illustrating a possible alternative approach by retranslating one chapter. In 1997 Michael Pye defended his original work. Here I show that this defence misunderstands at least some of the rationale for suggesting an alternative translation method, and provide a short passage of translation with commentary from Hattori Somon (1724-1769), a very similar but much less well-known scholar, in order both to introduce his thought and to illustrate further the translation method I prefer. Finally some broader questions about the interpretation of Japanese eighteenth century thought are briefly indicated.